11-2x-6y=-11

Simple and best practice solution for 11-2x-6y=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-2x-6y=-11 equation:


Simplifying
11 + -2x + -6y = -11

Solving
11 + -2x + -6y = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -2x + -11 + -6y = -11 + -11

Reorder the terms:
11 + -11 + -2x + -6y = -11 + -11

Combine like terms: 11 + -11 = 0
0 + -2x + -6y = -11 + -11
-2x + -6y = -11 + -11

Combine like terms: -11 + -11 = -22
-2x + -6y = -22

Add '6y' to each side of the equation.
-2x + -6y + 6y = -22 + 6y

Combine like terms: -6y + 6y = 0
-2x + 0 = -22 + 6y
-2x = -22 + 6y

Divide each side by '-2'.
x = 11 + -3y

Simplifying
x = 11 + -3y

See similar equations:

| 2x-3/5=3x+2 | | 6a+4b-a+9b= | | 7(4x+9)=165 | | -1=28x+21 | | 7a-4=10-2a-41 | | -4v^2+28v+32=0 | | 12-x/8=-1 | | 3a-a+5-6= | | 4+49x=21x+16 | | 5(6x-4)=190 | | 4.2x=-24x-48 | | (9-u)(2u-1)=0 | | 4+49=21x+16 | | 5x^2+56x+27=0 | | X/3-5=5 | | 30b=5c | | 5(82.5)+3y=586.5 | | 3(12x+25)=205 | | 3x+32=15x+8 | | 3x+32=15x | | z^-4/3x^7 | | 5d-2d=6+3d | | x/3-4/x=4/3 | | x^3+12x-4=0 | | 18xy= | | 6y+13=11+5Y | | 3/8=n/16 | | 3(p+2)=3(2p-4)+4 | | 6m-4=-5(m+3) | | 26+x(17)=-42 | | 3(4x+7)=6x+75 | | 0.25x+90=1.25x |

Equations solver categories